Adjustments in the housing market after an environmental shock: evidence from a large-scale change in aircraft noise exposure - Almer, Christian Alexander; Boes, Stefan; Nüesch, Stephan (Oxford economic papers, 2017)
The impact of aircraft noise on housing is a much-debated topic. To meet the increasing demand for air transportation, airports seek to expand their capacities, but studies looking at market responses to a spatial redistribution of noise pollution are scarce. Using online advertisements of rental apartments around a large European airport (ZRH) and an unexpected change in flight regulations, we investigate the post-shock dynamics in apartment rents and tenants’ search behaviour. We find that rents take about two years to stabilise to a new equilibrium value. After this period there is a constant markup (discount) for apartments exposed to less (more) aircraft noise. Moreover, the number of advertisement clicks as a proxy for search behaviour and information acquisition is significantly higher during the adjustment period. Our results have implications regarding the calculation of capitalisation effects in quasi-experimental hedonic valuations, which need to take into account off-equilibrium periods.